(untitled) (Al-Aasar, 2025)
The Islamic judicial system is not merely a legal framework but a moral, spiritual, and divinely inspired institution established upon the foundations of Wahy (revelation) and the Sunnah of the Prophet Muhammad ﷺ. Within the vast corpus of Islamic jurisprudence, the discussions extending from Adab al-Qadha (judicial ethics and conduct) to Bayan ma yahilluhu al-Qadha wa ma la yahilluhu (matters permissible and impermissible in judicial verdicts) encompass the ethical, procedural, and substantive dimensions of justice. These themes collectively define the intellectual and moral identity of the Islamic judiciary. This study aims to investigate the sources, authentication, and scholarly foundations of these judicial principles by tracing their derivation (takhreej) from the Qur’an, the Prophetic traditions, the sayings of the Companions, and the classical juristic discourse. Furthermore, it examines the practical application and implementation (tatbiq) of these principles throughout Islamic legal history, highlighting how various schools of Islamic law interpreted and enforced them in judicial practice. The findings reveal that the judiciary in Islam is not merely an instrument of legal authority but an entrusted moral responsibility designed to ensure the supremacy of justice, preservation of human dignity, and balance within society. By critically analyzing the foundational sources and their juristic applications, the research underscores that the ethical and procedural principles of Islamic adjudication continue to offer a comprehensive and timeless model of justice—one capable of guiding contemporary judicial systems towards greater moral and ethical integrity. This research is primarily based on classical sources of Islamic jurisprudence, including fiqh, usul al-fiqh, and judicial literature, employing a qualitative and analytical methodology to explore the intellectual depth, authenticity, and contemporary relevance of the Islamic judicial framework.